Precambrian organisms and the isotopic composition of organic remains in the Ketilidian of South-West Greenland - Bondesen, Erling; Pedersen, Kaj Raunsgaard; Jørgensen, Ole (Meddelelser om Grønland, 1967)
The geological setting of organic remnants from well preserved Ketilidian rocks of SW Greenland is presented. The absolute age (2000 ? m. y.) of the rocks is discussed and compared to that of other regions. Many types of organic remnants have been found in these low-metamorphic rocks. Most of the organic remnants are microscopic globules and fragments with cell-like structures. The type which is best preserved is a complex globular structure on about 'f. mm in diameter. This structure is established as a new monotypic form genus Vallenia erlingi RAUNSGAARD PEDERSEN n. gen. et sp. Stromatolithes and other macro-structures of possible organic origin are also found. A coal-graphite layer indicates that large-scale accumulation of organic matter has taken place. The organic remnants are so well preserved that it has been possible to extract small amounts of paraffines (n-C11 to n-C31 with maximum about n-C18 to n-C20) and other organic compounds. The carbon-isotope composition from carbonaceous matter and carbonates from a number of samples has been determined. The analytical procedure is described. The result of this investigation shows 𝛿 C13-values which indicate that the carbonaceous material is probably of organic origin.